Effectiveness and limitations of human identification from cremains: A report of two cases. (November 2021) - Kumagai, Akiko; Izumisawa, Mitsuru; Takahashi, Noriaki; Biwasaka, Hitoshi
Highlights: This report comprising two cases describes the victim identification process of the 2011 Great East Japan Earthquake using the cremains. Case 1 showed that the identification could be assisted by establishing the age range of the cremains of maxilla by using CBCT images. Case 2 demonstrated that the deceased and the candidate were possibly the same person by the CBCT images of the cremated patella and the X-ray of the potential candidate. This report emphasises that PM data collection before cremation is extremely important, especially when large-scale disasters result in numerous casualties. Abstract: The present study of two case reports of the victims of the Great East Japan Earthquake demonstrates the effectiveness and limitations of using dental cone-beam computed tomography (CBCT) imaging of cremains as a means of identification. In case 1, identification was assisted by further expanding the age range of the cremains evaluated on macroscopy by obtaining CBCT images of the cremated maxilla. The findings of case 2 presented the possibility that the deceased and the candidate were the same person by superimposing the CBCT images of the cremated patella on the X-ray of the candidate. However, since cremated bones are deformed to varying degrees, it is clear that the images obtained before, rather than after, cremation are more effective in comparing post-mortem and ante-mortem images. Thus, it is necessary to collect extensive and diverse data on the deceased before cremation.